Implementation of a Character Education Strategy in the Perspective of Permendikbud Number 23 of 2015 at Raudhatul Athfal - Novan Ardy Wiyani (Tarbawi, 2020)
This study is aimed at obtaining a description of the various habituation activities carried out to form the character of students that are relevant to Permendikbud Number 23 of 2015 concerning Cultivation of Character. The research approach used is qualitative with the type of phenomenological research. Data were collected by interview, observation and documentation then analyzed using data analysis techniques Miles and Huberman's model. The results showed that there are seven strategies in implementing character education based on Permendikbud Number 23 of 2015. First, cultivating moral and spiritual values through habituation. Second, developing national values and diversity through habituation. Third, develop positive interactions between students and teachers and parents through habituation. Fourth, developing positive interactions between students through habituation. Fifth, taking care of yourself and the school environment through habituation. Sixth, develop the full potential of students through habituation. Seventh, the involvement of parents and the community in schools through habituation. The seven strategy activities have been implemented optimally because each of the objectives in them can be achieved.